Biomedical Applications: Tunable Delivery of siRNA from a Biodegradable Scaffold to Promote Angiogenesis In Vivo (Adv. Mater. 4/2014). (January 2014) - Nelson, Christopher E.; Kim, Arnold J.; Adolph, Elizabeth J.; Gupta, Mukesh K.; Yu, Fang; Hocking, Kyle M.; Davidson, Jeffrey M.; Guelcher, Scott A.; Duvall, Craig L.
<x xml:space="preserve">Abstract</x> On page 607, C. L. Duvall and co‐workers detail a new technology for sustained, local delivery of siRNA. The authors apply this platform to manipulate activity of a pro‐angiogenic transcription factor, which orchestrates robust biomaterial scaffold neovascularization in vivo. This system may provide a superior approach to traditional pro‐angiogenic therapies and holds promise for broader application in regenerative medicine. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>